Selective inhibition of DNA ligase IV provides additional efficacy to the treatment of anaplastic thyroid cancer - Sriramareddy, Sathya Neelature; Jamakhani, Majeed; Vilanova, Léa; Brossel, Hélène; Staumont, Bernard; Hamaidia, Malik (Frontiers in Oncology, 2024)
Although the incidence of anaplastic thyroid carcinoma (ATC) is low (2.5% of thyroid cancer cases), this cancer has a very poor prognosis (survival rates < 5 months) and accounts for 14-39% of deaths.Conventional therapies based on surgery in combination with radiotherapy or chemotherapy showed limited effectiveness primarily due to the robust and protective DNA damage response in thyroid cancer cells.We used single-cell transcriptomic data from patients with different subtypes of thyroid cancer to study expression of genes involved in homologous recombination (HR) and non-homologous end joining (NHEJ) pathways. Then, we investigated the mechanisms of DNA damage and repair in anaplastic (C643 and Hth74) and papillary (TPC-1) thyroid cancer cell lines. The effect of caffeine (inhibitor of ATM and ATR) and UCN-01 (CHK1 inhibitor) was evaluated in cell cycle progression of thyroid cancer cells after -radiation or doxorubicin treatment. The DNA damage response was monitored after staining of phosphorylated γ-H2AX and 53BP1. Reporter plasmids were used to determine the efficacy of double-strand DNA breaks (DSBs) repair by HR and NHEJ in thyroid cancer cells. We evaluated the combination of selective inhibition of the DNA ligase IV by SCR7 and doxorubicin on cellular apoptosis and tumor growth in xenograft murine models of anaplastic thyroid cancer.Single-cell RNA-Seq showed that NHEJ-and HR-related genes are expressed in ATC and PTC patients. We showed that ATC cells undergo mitosis in the presence of unrepaired DNA damage caused by -radiation and doxorubicin treatment. To proliferate and survive, these cells efficiently repair DNA lesions using homologous recombination (HR) and non-homologous end joining (NHEJ). The combination of SCR7 with doxorubicin, significantly increased apoptosis and impaired ATC tumor growth in a xenograft mouse model compared to doxorubicin monotherapy.This study shows the therapeutic value of the combination of a DNA ligase IV inhibitor and DNAdamaging agents (doxorubicin and/or γ-radiation) for the treatment of anaplastic thyroid cancer.